Incident reporting digitalization: the experience of an Italian academic hospital, 2019. (30th September 2020) - Ruscio, E; Bianchet, B; Scarpis, E; Del Pin, M; Degan, S; De Corti, D; Bellomo, F; Farneti, F; Cocconi, R; Brusaferro, S
Abstract: Issue: Incident reporting (IR) is an important tool to assess potential or current problems within health care facilities. To increase the number of IR should be an important issue of the risk manager. In the academic hospital Santa Maria della Misericordia (SMM) of Udine, in North-east of Italy, IR were anonymous paper forms handwritten by health-care workers (HCW) and sent to Clinical Risk Management by internal mail. Digitalization was carried out aiming to increase IR, making it simpler, more direct and perceived as more anonymous by HCW. Description of the problem: January 1st 2019 the digitized system was initialized, between January and March two training sessions for HCW were carried out and from the 1st April HCW began to send IR with the new application which was installed on every hospital's PC. The objectives were to push HCW to report more, mostly on their own wards' incidents, and to receive complete IR through the insertion of some mandatory information fields. Results: Comparison between the period from 1st April to 31th December 2018 and from 1st April to 31th December 2019 showed an increase of 22, 6% of IR (from 678 to 831), an increase of 11, 2% (from 331 to 368) of IR regarding problems with other wards or services and an increase of 33, 4% (from 347 to 463) of IR regarding their own wards' incidents. Lessons: Digitalization seems to be appreciated by HCW despite they are forced to give more information due to the mandatory fields. This could be explained considering that a direct incident reporting system ensures privacy of the HCW which feels more warded also when he reports an internal problem of his own ward. Finally, mandatory fields facilitate risk management work giving all the relevant information about the incident. Key messages: Digital reporting seems appreciated by HCW and could be a mean to increase the number of incident reporting. To guarantee the anonimity of incident reporting should be a priority and every way to make the HCW feel anonymous seems to be appreciated.